Design of a snack seasoning mixing machine for culinary partners - Agistina, Jesika Tri; Rofik, Ainur; Pandu, Moh. Setya; Suistiawan, Agus (Privietlab, 2026)
To improve customer satisfaction, this study discusses the design of a snack seasoning mixing machine to improve the efficiency and consistency of the mixing process in the food industry. The main problems faced by businesses are uneven seasoning distribution and long production times when the process is performed manually. The methods used included identifying user needs, mechanical and electrical design, material selection, and prototype development using an electric motor as the main drive and mixing shaft in a stainless steel container. Testing was conducted to determine the machine's performance in mixing seasonings. The results showed that the machine was able to mix seasonings within 2-3 minutes with stable operation, low power consumption, and produced a more homogeneous mixture compared to the manual process. In addition, the machine is easy to operate and maintain, making it suitable for application in small- and medium-sized businesses. The conclusion of this study is that the designed snack seasoning mixer has good performance, is capable of improving production quality and efficiency, and has the potential to be further developed to increase its capacity and durability.